Pelatihan dan Sosialisasi Pengurusan Jenazah: Meningkatkan Pemahaman dan Keterampilan dalam Pengurusan Jenazah bagi Siswa Madrasah - Azhari, Mohd. Fikri; Riyawi, Mohd. Rafi; Fitri, Yona; Azhari, Mawaddah Warohmah (Universitas Pahlawan Tuanku Tambusai, 2026)
The management of the deceased is a collective obligation (fardhu kifayah) that every Muslim must understand, including madrasah students as future bearers of religious values. However, students’ awareness and practical skills regarding funeral management remain limited, requiring a structured educational program. This study aims to describe the implementation of training and socialization on funeral management for madrasah students and to analyze improvements in their understanding and skills. The research employed a Participatory Action Research (PAR) approach using pre‐tests, post‐tests, and direct observation. The findings indicate significant improvement in students’ cognitive, affective, and psychomotor aspects, demonstrated by better knowledge of Islamic procedures for washing, shrouding, praying over, and burying the deceased. Students also exhibited greater readiness and confidence in performing these practices within the community. Thus, the training program effectively enhances students’ religious competence and character development.